PV in Combination with Micro Wind Turbines for Rural Household Electrification in the Northeast of Brazil - Krauter, Stefan; Calvacante, F. S. A.; Cunha, M. S.; de Lima, L. C. (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3532)

Renewable Energy in Latin America - Krauter, Stefan; Kissel, J. (Renewable Energy World)

Activities concerning the Set-up of an International University for Renewable Energy - Krauter, Stefan (Proceedings of the International Seminar on Hydrogen Technologies, Buenos Aires (Argentina), 7.–9. September 2004)

Security Aspects of Internet Voting - Schryen, Guido (37th Annual Hawaii International Conference on System Sciences)
Voting via the Internet has become a feasible option for political as well as non-political ballots. However, there are many obstacles which have to be overcome, especially legal restrictions have to be transformed into technical and security solutions. The article starts with a brief presentation of advantages and disadvantages of Internet ballots and presents application fields and pilot schemes. Then, technological security aspects are derived due to democratic basic principles. Especially the applied voting procedures are critical in security terms. Hence, the most relevant cryptographic protocols are presented and their drawbacks and shortcomings are identified. However, this article does not propose a new voting protocol. Beyond fixing cryptographic procedures for ballots, more elements are to be specified, e.g. responsibilities and rights of involved authorities or security precautions regarding hardware and software. For this reason, a structural security framework for electronic voting systems is presented which can be used for their composition and analysis.

Internationalisierung mittelständischer Unternehmen: Fünf Thesen zum Auslandsmarkterfolg - Kabst, Rüdiger

International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des "Cranfield Projects on International Human Resource Management" - Kabst, Rüdiger; Brewster, C (Handwörterbuch des Personalwesens)

The Netherlands and Germany: Flexibility or Rigidity - Dietz, B; Hoogendoorn, J; Kabst, Rüdiger; Schmelter, A (Human Resource Management in Europe: Evidence of Convergence?)

Transaktionskostentheorie: Einführung, kritische Diskussion und Ansätze zur Weiterentwicklung - Kabst, Rüdiger (Personaltheorie als Beitrag zur Theorie der Unternehmung)

Theoretical Perspectives for Human Resource Management: The German Discussion - Kabst, Rüdiger; Weber, W (Management Revue: The International Review of Management Studies.)

SIMULTANEOUSLY MODELING CONDITIONAL HETEROSKEDASTICITY AND SCALE CHANGE - Feng, Yuanhua (Econometric Theory)

Non- and Semiparametric Regression with Fractional Time Series Errors - Feng, Yuanhua

A robust data-driven version of the Berlin Method - Heiler, Siegfried; Feng, Yuanhua (Zeitreihenanalyse in der empirischen Wirtschaftsforschung)

Wettbewerbsfähigkeit und Dynamik institutioneller Standortbedingungen: Ein empirischer Test des „Varieties-of-Capitalism “-Ansatzes - Paunescu, Mihai; Schneider, Martin (Schmollers Jahrbuch: Journal of Applied Social Science Studies/Zeitschrift für Wirtschafts-und Sozialwissenschaften)

Occupational job creation: patterns and implications - Fahr, Rene; Sunde, Uwe (Oxford Economic Papers)

A Comparative Analysis of Job Entry Methods in Japan, the US and Europe (Japanese) - Toshihiro, KODAMA; Yoshio, HIGUCHI; Masahiro, ABE; Fahr, Rene

Loafing or Learning? - Fahr, Rene (The Economics of Time Use)

Wettbewerbsfähigkeit und Dynamik institutioneller Standortbedingungen: Ein empirischer Test des „Varieties-of-Capitalism “-Ansatzes - Paunescu, Mihai; Schneider, Martin (Schmollers Jahrbuch: Journal of Applied Social Science Studies/Zeitschrift für Wirtschafts-und Sozialwissenschaften)

Wertorientiertes Beziehungsmarketing in Kunden-Lieferantenbeziehungen. - Eggert, A

The Evolution of Relationship Marketing and the International Colloquia - Bliemel, Friedhelm; Eggert, Andreas; Fassott, Georg; Ballantyne, David (Journal of Relationship Marketing)

Dynamic Meta Modeling with Time: Specifying the Semantics of Multimedia Sequence Diagrams - Hendrik Hausmann, Jan; Heckel, Reiko; Sauer, Stefan (Software and Systems Modeling)
UML offers different diagram types to model behavior and dynamics of software systems. In some domains like embedded real-time systems or multimedia systems, it is necessary to include specifications of time since the correctness of these applications depends on the fulfillment of temporal requirements in addition to functional requirements. UML thus already incorporates language features to model time and temporal constraints. Such model elements must have an equivalent in the semantic domain. We have proposed Dynamic Meta Modeling (DMM) as a means for the specification of the formal operational semantics of UML models by applying graph transformation to the meta modeling of dynamic behavior. Within this paper, we extend this approach to also account for time by building on timed graph transformations. We apply these concepts to the domain of multimedia application modeling in which we adopt UML sequence diagrams. The DMM rules with time then specify an interpreter that can be used to analyze or test a model of multimedia sequence diagrams.